Utilizing Water Activity as a Simple Measure to Understand Hydrophobicity in Ionic Liquids - Han, Qi; Wang, Xungai; Bynre, Nolene (Frontiers in Chemistry, 2019)
Ionic liquids (ILs) are regarded as designable solvents finding use in a variety of applications. One of the challenges of the design and selection process is to understand the ionic liquid properties. In this work, we selected seven ILs containing three types of hydrophilic anions and examined several key properties, which are correlated to hydrophobicity. In particular, we measured the hydrogen bond basicity β and water activity aw of IL and IL-water mixtures, and suggested that these two properties are linearly correlated. We then used NMR to evaluate the chemical shift of H2O in hydrated ILs. Correlating the outcomes of each of these techniques with respect to understanding the hydrophobicity of the ILs is discussed. It is shown that water activity aw is the most facile technique to represent and understand hydrophobicity of ILs.